2021
DOI: 10.1007/s00417-021-05276-z
|View full text |Cite
|
Sign up to set email alerts
|

Retinal nerve fibre layer thickness measurements in childhood glaucoma: the role of scanning laser polarimetry and optical coherence tomography

Abstract: Purpose A central diagnostic tool in adult glaucoma is the peripapillary retinal nerve fibre layer (pRNFL) thickness. It can be assessed by scanning laser polarimetry (SLP) or optical coherence tomography (OCT). However, studies investigating the relevance of pRNFL measurements in children are rare. This study aims to compare the glaucoma diagnosing ability of SLP and OCT pRNFL thickness measurements in a paediatric population. Methods This retrospective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…[ 7 8 9 ] Lever et al . [ 26 ] reported that parapapillary RNFL thickness was decreased in the superior, nasal, and inferior quadrants of childhood glaucoma patients compared to healthy controls. Srinivasan et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 8 9 ] Lever et al . [ 26 ] reported that parapapillary RNFL thickness was decreased in the superior, nasal, and inferior quadrants of childhood glaucoma patients compared to healthy controls. Srinivasan et al .…”
Section: Discussionmentioning
confidence: 99%
“…Литературные данные об изменениях параметров ОКТ при ПВГ и возможности их использования для диагностики и оценки прогрессирования ГОН противоречивы и основаны на небольшом клиническом материале [7][8][9][10][11].…”
unclassified